Accelerated dynamic cardiac MRI exploiting sparse-Kalman-smoother self-calibration and reconstruction (k − t SPARKS) - Park, Suhyung; Park, Jaeseok (Physics in medicine & biology, 2015)
Accelerated dynamic MRI, which exploits spatiotemporal redundancies in k  −  t space and coil dimension, has been widely used to reduce the number of signal encoding and thus increase imaging efficiency with minimal loss of image quality. Nonetheless, particularly in cardiac MRI it still suffers from artifacts and amplified noise in the presence of time-drifting coil sensitivity due to relative motion between coil and subject (e.g. free breathing). Furthermore, a substantial number of additional calibrating signals is to be acquired to warrant accurate calibration of coil sensitivity. In this work, we propose a novel, accelerated dynamic cardiac MRI with sparse-Kalman-smoother self-calibration and reconstruction (k  −  t SPARKS), which is robust to time-varying coil sensitivity even with a small number of calibrating signals. The proposed k  −  t SPARKS incorporates Kalman-smoother self-calibration in k  −  t space and sparse signal recovery in x  −   f space into a single optimization problem, leading to iterative, joint estimation of time-varying convolution kernels and missing signals in k  −  t space. In the Kalman-smoother calibration, motion-induced uncertainties over the entire time frames were included in modeling state transition while a coil-dependent noise statistic in describing measurement process. The sparse signal recovery iteratively alternates with the self-calibration to tackle the ill-conditioning problem potentially resulting from insufficient calibrating signals. Simulations and experiments were performed using both the proposed and conventional methods for comparison, revealing that the proposed k  −  t SPARKS yields higher signal-to-error ratio and superior temporal fidelity in both breath-hold and free-breathing cardiac applications over all reduction factors.